Kondisi Keuangan dan Lingkungan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Agustina Fatima (AFRE (Accounting and Financial Review), 2019)
Tax compliance is the attitude of someone who shows that they are obedient in fulfilling their tax obligations, based on rules and regulations in taxation. This study aims to determine the effect of financial conditions and environmental on the compliance of individual taxpayers in paying land and building tax in Salatiga city. The object of this research is the individual taxpayer who is charged for land and building tax in Salatiga. The method used in the research is multiple regression test, to see the effect of financial conditions and environmental on compliance in paying land and building taxes. The data source used is primary data, which is obtained through disturbing questionnaires directly to respondents. The results of this study provide evidence that financial conditions and environmental affect the compliance of individual taxpayers in paying land and building taxes in the city of Salatiga DOI: https://doi.org/10.26905/afr.v2i2.3172